Fatigue induced by a simulated competition in elite world-class fencers - Varesco, G.; Pageaux, B.; Goisbault, M.; Martinent, G.; Doron, J.; Jubeau, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Fencing is an open-skilled, asymmetric combat sport characterized by high-intensity bouts and requires high levels of coordination, power, and accuracy. However, the performance-specific fatigue of fencing remains to be elucidated1. In the present study, we evaluated the neuromuscular and mental aspects of fatigue induced by a competition in elite world-class athletes.